(3aJM GdEdg HYOI eG jfOQL ef GdYbGFO aj dG Edg EdG Gddg eMeO QShd Gddgs - (3CMeO Hf YHO GdaJGM Hf jhSa Hf YeQ Gdedhis; (3GdeLjQj , TgGH GdOjf CHh GdYHGS CMeO Hf YHO GdaJGM Hf jhSa Hf YeQ Gdedhj GdTGaYj,J (B1181 (3g` s
(3ChdgG (B:s
(3hHYO jbhd GdYHO GdabjQ Edi ehdGg CMeO Hf YHO GdaJGM gPg fHPg ai EfOQGL GdYbGFO ai dG Edg EdG Gddg eMeO QShd Gddg s
(3BNQgG (B:s
(3aMGUd eG jfOQL ai eMeO QShd Gddg hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B152 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B278s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B_ (3GdQHGW (B(105) s
Keywords: (3GdJhMjO hGdedd hGdfMds